SPIDERplan: A tool to support decision-making in radiation therapy treatment plan assessment - Ventura, Tiago (2019)
Aim In this work, a graphical method for radiotherapy treatment plan assessment and comparison, named SPIDERplan, is proposed. It aims to support plan approval allowing independent and consistent comparisons of different treatment techniques, algorithms or treatment planning systems. Background Optimized plans from modern radiotherapy are not easy to evaluate and compare because of their inherent multicriterial nature. The clinical decision on the best treatment plan is mostly based on subjective options. Materials and methods SPIDERplan combines a graphical analysis with a scoring index. Customized radar plots based on the categorization of structures into groups and on the determination of individual structures scores are generated. To each group and structure, an angular amplitude is assigned expressing the clinical importance defined by the radiation oncologist. Completing the graphical evaluation, a global plan score, based on the structures score and their clinical weights, is determined. After a necessary clinical validation of the group weights, SPIDERplan efficacy, to compare and rank different plans, was tested through a planning exercise where plans had been generated for a nasal cavity case using different treatment planning systems. Results SPIDERplan method was applied to the dose metrics achieved by the nasal cavity test plans. The generated diagrams and scores successfully ranked the plans according to the prescribed dose objectives and constraints and the radiation oncologist priorities, after a necessary clinical validation process. Conclusions SPIDERplan enables a fast and consistent evaluation of plan quality considering all targets and organs at risk.